Lymphadenitis in children is caused by Mycobacterium avium hominissuis and not related to ‘bird tuberculosis’ - Bruijnesteijn van Coppenraet, L. E. S. (Springer-Verlag, 2008)
Mycobacterium avium is the most commonly encountered mycobacterium species among non-Mycobacterium tuberculosis complex (nontuberculous mycobacteria) isolates worldwide and frequently causes lymphadenitis in children. During a multi-centre study in The Netherlands that was performed to determine the optimal treatment for mycobacterial lymphadenitis, concern was expressed in the media about the possible role of birds as sources of these M. avium infections, referred to as ‘bird tuberculosis.’ To examine the involvement of birds in mycobacterial lymphadenitis, 34 M. avium isolates from lymphadenitis cases were subjected to IS1245 restriction fragment length polymorphism (RFLP) typing. This genotyping method enables the distinction of the subspecies M. avium subsp. hominissuis and the ‘bird-type’ M. avium spp. avium. Highly variable RFLP patterns were found among the lymphadenitis M. avium isolates, and all belonged to the M. avium hominissuis subspecies. A relation to pet birds in the etiology of mycobacterial lymphadenitis could not be established, and the source of the infections may be environmental.